Oral Health Care Utilization During the First Decade of Thai Universal Health Coverage System - Lapying, Phenkhae; Putthasri, Weerasak (Journal of Health Science of Thailand, 2017)
The objective of this study was to analyze the utilization of oral health care in Thai population during the first decade of the universal health coverage system using database of the Health and Welfare Surveys carried out by the National Statistic Office in the year 2003, 2007 and 2011. The surveys covered 26,520 households selected by stratified two-stage sampling. The data were then weighted to represent the total population. It was found that Thai people decreased oral health care utilization in 2007 (8.69%) and increased in 2011 (9.28%) but still lower than in 2003 (10.19%). Women had utilization rates higher than male. Based on age, the 15-24 age group increased the utilization in 2011. The 5-14 age group in particular had higher utilization rates than other groups in 2003 and 2007, but the rates still decreased continually. Elderly increased the utilization in 2007 and decreased in 2011. While 0-4 age group still had low utilization rate during the three years. In Bangkok, increasing highest utilization rates in the three surveys were observed. The latest rate and frequency were 14.42 percent and 0.27 visit/person/year. In contrast, the Northeast rates were decreasing to reach the lowest in 2011. In 2007, people in other regions increased the utilization but still lower than that of the year 2003. In 2011, top four facilities that people sought the services were private dental clinics, community hospitals, general or regional hospitals and health post or community health center having dental personnel. The average care cost was 493 baht per visit that lower than 738 baht per visit in 2007. Among the 3 major health insurance schemes (the Universal health Coverage - UCS, the Social Security and the Civil Service Medical Benefit), the beneficiaries of UCS had lowest accessibility in all the three years (9.18%, 7.57% and 8.08%, respectively). In addition, non-utilization of the UCS entitlements in the last dental care service were also increasing (27.70%, 31.14% and 33.53% in 2003, 2007 and 2011, respectively). Social Security beneficiaries had greater accessibility in 2011 and got better benefits than those of the Civil Servant Medical Benefit Scheme.